2022
DOI: 10.3390/s22124479
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Hyperspectral Method to Detect Moldy Core in Apple Fruits

Abstract: An innovative low-cost device based on hyperspectral spectroscopy in the near infrared (NIR) spectral region is proposed for the non-invasive detection of moldy core (MC) in apples. The system, based on light collection by an integrating sphere, was tested on 70 apples cultivar (cv) Golden Delicious infected by Alternaria alternata, one of the main pathogens responsible for MC disease. Apples were sampled in vertical and horizontal positions during five measurement rounds in 13 days’ time, and 700 spectral sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…They found that the artificial neural network pattern recognition (ANN-AP) model combined with the infection growth rate showed a predictive accuracy of 100% at round 1 and 97.15% at round 2 for diseased apples. The research results indicate that the model exhibits consistency in infection rate and development on the test set, thus having greater potential for industrial applicability [33]. Tian et al designed an online NIR transmission spectroscopy system for detecting apple mold heart disease.…”
Section: Nir Spectroscopymentioning
confidence: 93%
“…They found that the artificial neural network pattern recognition (ANN-AP) model combined with the infection growth rate showed a predictive accuracy of 100% at round 1 and 97.15% at round 2 for diseased apples. The research results indicate that the model exhibits consistency in infection rate and development on the test set, thus having greater potential for industrial applicability [33]. Tian et al designed an online NIR transmission spectroscopy system for detecting apple mold heart disease.…”
Section: Nir Spectroscopymentioning
confidence: 93%
“…Andrea et al designed and manufactured a low-cost innovative device for early detection based on near infrared spectroscopy technology. After multiple rounds of detection, it was found that the ANN-AP model combined with the infection growth rate showed a better correlation, with the highest accuracy and a prediction accuracy of 97% [18] . Tian et al designed and assembled an online spectral measurement system for apple mold heart disease using near-infrared transmission spectrum technology.…”
Section: Near Infrared Spectroscopymentioning
confidence: 99%
“…AP-induced reflectance changes due to leaf reddening can be detected using RGB cameras, as they are visible to the human eye. Multispectral and hyperspectral imaging may yield potentials for early detection as well as improved discrimination from other stresses [20][21][22]. However, focusing on a single symptom requires prior investigation of its significance.…”
Section: Introductionmentioning
confidence: 99%